Evaluation of Development Index of China’s VC Industry Based on Weight Optimization Algorithm and TOPSIS - Yi Sun; Long-Long Zhou; Shan Zhu; Jin-Tao Su; Jing Zhang (Complexity)
After more than 20 years of rapid growth in China’s venture capital industry, huge market development potential and boost by the digital wave have made China one of the most attractive venture capital markets in the world. At present, most of the measurement and evaluation of the development level of China’s venture capital industry are qualitative evaluations and few quantitative evaluations, and the evaluation indicators are unitary. It is difficult to comprehensively measure the development status of the entire venture capital industry. This paper constructs a comprehensive evaluation model of China’s venture capital industry development index to reflect the development status of the entire industry, while dynamically tracking its future development trends. In the index system of China’s venture capital industry development index model, there are a total of ten indicators in three aspects: total, structural, and performance dimension. The calculation results are obtained by subjective and objective weighting target planning algorithm, and the final score evaluated by TOPSIS model is indexed. In this way, the development curve of China’s venture capital industry from 2006 to 2016 is obtained. Judging from the results reflected in the model conclusions, the index can better reflect the current development trend and problems faced by China’s venture capital industry.